Substance addiction and human evolution - Mutlu, Elif (Journal of Dependence, 2018)
Today, substance addiction is one of the major problems that affects the human population multidirectionally and deeply. The use of the addictive substances for various purposes dates back to the times when the fist human communities lived. When some of the main issues that have taken places throughout the history are examined, such as the coevolution between the psychotropic plants and mankind the signs that this process leaves on the human organism, the evolution of addiction related brain structures such as amygdala in vertebrate organisms and the neuroadaptation mechanisms that operate in the addiction process; the evolutionary dimensions of the substance addiction comes into question. When this behavior of humanbeing as a living being subject to the evolutionary process is evaluated from an evolutionary perspective, specific adaptation, natural selection, and survival mechanisms are similar to those that take an active role in the substance addiction process. It is aimed to investigate the preservation mechanisms of substance addiction and therefore to bring a novel sight to the substance addiction issue with this study.
Keywords: evolutionary psychology; neurobiology of addiction; substance addiction; theory of evolution